Top Training Needs of the Governmental Public Health Workforce. (March 2019) - Bogaert, Kyle; Castrucci, Brian C.; Gould, Elizabeth; Rider, Nikki; Whang, Christina; Corcoran, Elizabeth
Abstract : Context: Workforce development in governmental public health has historically focused on discipline-specific skills. However, as the field of public health has evolved, crosscutting skills have become critical. The 2017 fielding of the Public Health Workforce Interests and Needs Survey (PH WINS) provides a national benchmark for gaps in crosscutting skills in state and local health departments. Objective: The purpose of this article is to identify top areas of training needs in the governmental public health workforce using data from PH WINS 2017. Design: PH WINS participants in state and local health departments were surveyed in fall 2017 using a Web-based platform. Balanced repeated replication weights were used to account for complex sample design. Setting: Forty-seven state health agencies, 26 large city health departments, and a nationally representative sample of mid-to-large local health departments. Participants: Permanently employed governmental public health staff. Main Outcome Measures: Training needs were determined by combining self-reported skill importance and proficiency. Skills reported to be of high importance, and low levels of proficiency were coded as training needs. Focus area gaps were defined as having a training need in at least one skill in the focus area. Results: The largest area of training need, regardless of supervisory status, was in budgeting and financial management (55%; 95% confidence interval [CI], 53-56), with a large gap also identified in systems and strategic thinking (49%; 95% CI, 47-50). There was some variation by supervisory status, with training needs for nonsupervisors in change management and in developing a vision for a healthy community for management. Conclusions: The PH WINS training needs assessment provides the first nationally representative data on training needs for the state and local health department workforce. Across state and local health departments, there are common critical training needs essential for the current and future practice of public health.